Zoo II - Patterson, James, 1947-; DiLallo, Max (New York : Bookshots/Little, Brown and Company, 2016)
With the planet still under attack by vicious animals, humans begin evolving into a barbaric species that has the power to save civilization--or destroy it.
Keywords: Aggressive behavior in animals -- Fiction; Human-animal relationships -- Fiction; Biologists -- Fiction; Ecologists -- Fiction; Suspense fiction